Preliminary characterization of lysosomal-related genes in two tay sachs variant B1 fibroblast cell lines - Ribeiro, Diogo (2022)
Aim: The present work focus on the NGS characterization of lysosomal-related genes in two skin fibroblast cell lines from TSD variant B1 patients with the mutation p.R178H prior to the manipulations to generate hiPSCs and NPCs. Registering the gene variants at “time zero” will allow the eventual detection of future alterations.